Synthesis and Crystallography of 1-acetoxy-3-ethoxy carbonyl-4-(4-methoxy)phenyl-7-methoxynaphthalene - Singh, Ashok Kumar (Journal of Nepal Chemical Society, 2013)
1-Acetoxy-3-ethoxy carbonyl-4-(4-methoxy)phenyl-7-methoxynaphthalene (3) has been synthesized and characterized by X-ray diffraction method . The compound crystallizes in triclinic space group P-1 with cell parameter a = 7.793 (6) Å, b = 10.7428(16) Å, c = 13.306 (4) Å and Z = 2. DOI: http://dx.doi.org/10.3126/jncs.v28i0.8115 Journal of Nepal Chemical Society Vol. 28, 2011 Page: 102-105 Uploaded Date: May 24, 2013